Enhanced Bit Repair IP Fast Reroute Mechanism for Rapid Network Recovery - Jozef Papan; Pavel Segec; Michal Kvet (Applied Sciences, 2021)
The massive development of virtualized infrastructures, Internet of Things (IoT), and Wireless Sensor Network (WSN) in recent years has led to an increase in quality requirements for the management and reliability of underlay communication networks. Existing converged networks must therefore guarantee specific quantitative and qualitative parameters of different network communication services to meet customer requirements. However, the quality of the services operated is very negatively affected by an unpredictable failure of a communication link or a network node. In such situations, communication is typically interrupted for a period that is difficult to predict, and which can lead to significant financial losses and other negative effects. Internet Protocol Fast Reroute (IP FRR) technology was developed for these reasons. The paper presents the proposal of the new Enhanced Bit Repair (EB-REP) IP FRR mechanism, which offers significant improvements over its predecessor, the B-REP mechanism. The B-REP offers protection against a single failure and only for selected critical IP flows. The EB-REP provides advanced protection against multiple failures in a protected network domain and the protection can be provided for all network flows. The EB-REP calculates alternative paths in advance based on link metrics, but also allows the construction of alternative paths independently of them. The construction of alternative FRR paths uses a standardized tunneling approach via a unique field Bit-String. Thanks to these features, EB-REP is an advanced contribution to solving IP FRR-related problems, which enables the use of EB-REP in many network deployments, but especially in network solutions that require reliable data transmission.